PROSES LEGISLASI DPRD KOTA PEKANBARU DALAM PEMBENTUKAN PERATURAN DAERAH KOTA PEKANBARU TAHUN 2013 - Riandi Adma Tri Saputra; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Legislation is an interesting process studied to determine how the role of Parliament as the party legislators in the creation and establishment of local regulations. In 2013 There are 13 Ranperda which will be discussed and 10 of them come from the executive or the City of Pekanbaru and only 6 Ranperda passed into law. This study aimed to see how the dynamics of the legislative process in 2013. This study used a qualitative method and conducted in the city of Pekanbaru.This study uses informants as sources of information objects that aims to achieve mastery in getting information. Data used in this study are primary data and secondary data obtained through direct observation and interviews with informants.Analysis of the data in a descriptive study conducted by describing the data in a systematic and objective so as to produce factual information, current, and accurate. Based on the results of the study found the following matters; First, exercising the function of legislation or regulation setting process Pekanbaru City in 2013 in general can not be concluded in accordance with expectations because there are many discussions Ranperda The delay so that the establishment has not done thoroughly. This is caused by the time the Management of Pekanbaru City Council is not running optimally. Second, the role and function of the maximum yet Pekanbaru City Council, due to factors of quality of Human Resources (HR), and Rule Parliament is too detailed, so it seems rambling in Ranperda formation.Keyword: Legislation, Parliament, Pekanbaru